Additive or multiplicative? Predicting academic outcomes from self-regulation and context. (September 2021) - Davisson, Erin K.; Hoyle, Rick H.; Andrade, Fernanda
Abstract: Many studies have documented the role of self-regulation in predicting academic outcomes. However, fewer have comprehensively measured self-regulation or considered it simultaneously with contextual variables to test formally the often-advanced "risk-buffering" hypothesis, wherein self-regulatory skill protects against contextual risk factors. In a large, regionally representative sample of U.S. adolescents, we linked self-reported demographics, self-regulation, and academic outcomes to Census data assessing neighborhood context and administrative data measuring economic disadvantage and achievement levels on state end-of-grade tests. We find inconsistent evidence for a risk-buffering role of self-regulation in the prediction of academic outcomes. Rather, we demonstrate that self-regulation is independently associated with academic outcomes, even when controlling for demographics and context. Highlights: We combined survey, administrative, and Census data in a representative sample of adolescents. We tested independent and joint effects of context and self-regulation on academics. Our comprehensive self-regulation measure was uniquely associated with academic outcomes. Higher self-regulation was associated with better academic outcomes across context. The self-regulation effect was consistent, even when controlling for demographics and context.